Efficacy and safety of novel temperature-controlled radiofrequency ablation system during pulmonary vein isolation in patients with paroxysmal atrial fibrillation: TRAC-AF study - Starek, Zdenek; Lehar, Frantisek; Jez, Jiri; Pesl, Martin; Neuzil, Petr; Sediva, Lucie; Petru, Jan; Dujka, Libor; Funasako, Moritoshi; Kautzner, Josef; Peichl, Petr; Aldhoon, Bashar; et al. (Journal of interventional cardiac electrophysiology, 2022)
BACKGROUND AND PURPOSE: Saline-irrigated radiofrequency ablation (RFA) for atrial fibrillation (AF) is limited by the absence of reliable thermal feedback limiting the utility of temperature monitoring for power titration. The DiamondTemp (DT) ablation catheter was designed to allow efficient temperature-controlled irrigated ablation. We sought to assess the 1-year clinical safety and efficacy of the DT catheter in treating drug-refractory paroxysmal AF. METHODS: The TRAC-AF trial (NCT02821351) is a prospective, multi-center (n = 4), single-arm study which enrolled patients with symptomatic, drug-refractory, paroxysmal AF. Using the DT catheter, point-by-point ablation was performed around all pulmonary veins (PVs) to achieve PV isolation (PVI). Ablation was performed in a temperature-controlled mode (60 °C, max 50 W). Acute and chronic efficacy and safety was evaluated. RESULTS: Seventy-one patients (age 69.9 ± 11.0 years; 60.6% male) were ablated using the DT catheter. The mean fluoroscopy and RF ablation times were 9.3 ± 6.1 min and 20.6 ± 8.9 min, respectively. Acute isolation of all PVs was achieved in 100% of patients, and freedom from AF after 1 year was 70.6%. There were no steam pops, char, or coagulum on the catheter tip after ablation. There were few serious procedure/device-related adverse events including a single case of cardiac tamponade (1.4%) and transient ischemic attack (1.4). CONCLUSION: This first in man series demonstrates that temperature-controlled irrigated RFA with the DT catheter is efficient, safe, and effective in the treatment of paroxysmal AF. Randomized controlled trials are ongoing and will evaluate better the role of this catheter in relation to standard RFA. TRIAL REGISTRATION: Registered on the site ClinicalTrials.gov January 2016 with identifier: NCT02821351.
Keywords: Diamond tip irrigated catheter; Humans; lidé středního věku; Temperature; venae pulmonales; Equipment Design; Catheter radiofrequency ablation; teplota; Aged; Female; výsledek terapie; senioři; lidé; Atrial Fibrillation; Safety and efficacy; katetrizační ablace; Temperature contol ablation; ženské pohlaví; Male; Middle Aged; Pulmonary Veins; Treatment Outcome; design vybavení; High-resolution electrograms; Aged, 80 and over; senioři nad 80 let; mužské pohlaví; prospektivní studie; Catheter Ablation; Atrial fibrillation; fibrilace síní; Prospective Studies